The Influence of Organizational Culture and Leadership on Police Member Integrity (Study: Rokan Hulu Police Department) - Ade Alfarisi; Abshor Marantika; Kasmawati Kasmawati (Dinasti Review, 2025)
The integrity of Indonesian National Police (Polri) members refers to attitudes and behaviors that reflect honesty, consistency, responsibility, and a high moral commitment in carrying out their duties and authority as law enforcers, protectors, guardians, and servants of the public. Many factors influence the integrity of Indonesian National Police (Polri) members, but this study focuses only on organizational culture and leadership. This research was conducted at the Rokan Hulu Police Department and aimed to determine and analyze: 1) the influence of organizational culture on the integrity of Indonesian National Police members; 2) the influence of leadership on the integrity of Indonesian National Police members; 3) the simultaneous influence of organizational culture and leadership on the integrity of Indonesian National Police members; and 4) the dominant factors, among organizational culture and leadership, that influence the integrity of Indonesian National Police members. This study used primary and secondary data obtained through interviews, questionnaires, observation, and documentation. The population of this study was all police officers at the Rokan Hulu Police Department. Using the Slovin formula, 81 police officers were selected as samples. The sampling method used was an accidental sampling method. The data analysis tool used was a multiple linear regression model, and hypothesis testing was conducted using the t-test, the F-test at 5% alpha, and the correlation coefficient (R) and the coefficient of determination (R2). The results of this study concluded that: 1) there is a significant influence of organizational culture and leadership variables on the integrity of police officers; 2) there is a significant influence of leadership variables on the integrity of police officers; 3) there is a significant simultaneous influence of organizational culture and leadership variables on the integrity of police officers; and 3) organizational culture has a dominant influence compared to leadership on the integrity of police officers at the Rokan Hulu Police Department. Furthermore, there is a strong positive relationship between organizational culture and leadership and police officer integrity, and there is a significant contribution of organizational culture and leadership to police officer integrity, as evidenced by the coefficient of determination of 75.1%.